2021
DOI: 10.47836/pjssh.29.2.30
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Online Interethnic Interactions on Interethnic Bridging Social Capital: A Study of Academic Staff in Malaysian Private Universities

Abstract: For decades, the uniqueness of Malaysia’s multiethnic, multilingual, and multicultural characteristics have been the focus of thinkers and policymakers in their effort towards nation-building. Such effort has been complemented by the contribution of researchers who provide relevant data and findings. Though the area of interethnic relations and interactions in Malaysia has been well researched, there is a gap in the literature regarding online interethnic relations and its role in bridging social capital. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…It is also consistent with the study of Mekrueang, Khaenamkhaew, Dechochai, & Damrongwattana (2 0 2 0 ) . It found that community storytelling reflects economic, social, and cultural, and it is consistent with the study of Luan, Halim, & Hafif (2021), It found that the uniqueness and its role in bridging social capital. These beliefs, values, and lifestyles developed and changed over time to become valuable lifelong learning sources, even if they changed slightly over time.…”
Section: Discussionsupporting
confidence: 80%
“…It is also consistent with the study of Mekrueang, Khaenamkhaew, Dechochai, & Damrongwattana (2 0 2 0 ) . It found that community storytelling reflects economic, social, and cultural, and it is consistent with the study of Luan, Halim, & Hafif (2021), It found that the uniqueness and its role in bridging social capital. These beliefs, values, and lifestyles developed and changed over time to become valuable lifelong learning sources, even if they changed slightly over time.…”
Section: Discussionsupporting
confidence: 80%